2010
DOI: 10.1152/ajpregu.00213.2010
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin restores branchial mitochondrion-rich cells expressing Na+/Clcotransporter in hypophysectomized Mozambique tilapia

Abstract: Hypophysectomy and hormone replacement therapy were conducted to investigate the regulation of branchial mitochondrion-rich cell (MRC) recruitment and hormone receptor expression in euryhaline tilapia (Oreochromis mossambicus). Gene expression and immunolocalization of Na(+)/Cl(-) cotransporter (NCC) and Na(+)/K(+)/2Cl(-) cotransporter (NKCC) were used as markers for freshwater (FW)- and seawater (SW)-type MRCs, respectively. In FW fish, hypophysectomy resulted in a significant drop in plasma osmolality, an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 43 publications
9
43
1
Order By: Relevance
“…These studies described the expression of either a sodium proton exchanger type 3 (nhe3) or a sodium chloride cotransporter (ncc) in two distinct FW-type MRCs. In accordance with their activity to support Cl K uptake in hypoosmotic environments (Horng et al 2009), Ncc-expressing MRCs are stimulated by oPrl injection (Breves et al 2010b). The drop in Na C , K C -ATPase a-1a mRNA during SW acclimation observed in this study correlates well with decreased ncc and nhe3 mRNA expression reported for larval and adult tilapia transferred to SW , Breves et al 2010a.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These studies described the expression of either a sodium proton exchanger type 3 (nhe3) or a sodium chloride cotransporter (ncc) in two distinct FW-type MRCs. In accordance with their activity to support Cl K uptake in hypoosmotic environments (Horng et al 2009), Ncc-expressing MRCs are stimulated by oPrl injection (Breves et al 2010b). The drop in Na C , K C -ATPase a-1a mRNA during SW acclimation observed in this study correlates well with decreased ncc and nhe3 mRNA expression reported for larval and adult tilapia transferred to SW , Breves et al 2010a.…”
Section: Discussionsupporting
confidence: 83%
“…Primer sequences were tested for nonspecific product amplification and primer-dimer formation by melting curve analysis; amplicon size was verified by agarose gel electrophoresis. Elongation factor 1a (ef-1a) primers have previously been reported (Breves et al 2010b). Additional primers used were (5 0 -3 0 ): b-actin (forward, CTCTT-CCAGCCTTCCTTCCT; reverse, ACAGGTCCTTACG-GATGTCG; amplicon sizeZ100 nt), acidic ribosomal phosphoprotein p0 (rplp0; forward, CCCCTTGTGATGT-GACAGTG; reverse, GTGATACCCAGAGCCTGGAA; amplicon sizeZ82 nt), Na…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…Expression of branchial prlr1 decreases with transfer from FW to SW (Breves et al 2010a) and increases with transfer from SW to FW (Breves et al 2011). Furthermore, branchial prlr1 levels decrease after hypophysectomy in SW but not in FW, suggesting that prlr1 expression is regulated, at least in part, by the pituitary (Breves et al 2010b). We found prlr1 in the RPD to be unresponsive either to salinity transfers in vivo or to changes in extracellular osmolality in vitro.…”
Section: Discussionmentioning
confidence: 67%
“…All primer pairs are previously described: prlr1 (Pierce et al 2007), prlr2 (long isoform; Breves et al 2010b), ostf1 (Breves et al 2010a), prl 177 and prl 188 (Magdeldin et al 2007) and ef1-a (Breves et al 2010b). The quantitative real-time PCRs were set up as previously described (Pierce et al 2007).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…The molecular mechanisms underlying the active absorption of Na C , Cl K , and Ca 2C have been investigated extensively over the past 80 years (for recent reviews see Evans (2011), Hwang et al (2011), Dymowska et al (2012) and Kumai & Perry (2012)). Based on these previous studies, it is clear that ion uptake is tightly regulated by several hormones, including prolactin (Pickford & Phillips 1959, Breves et al 2010, cortisol (Laurent & Perry 1990, Kumai et al 2012a, stanniocalcin ), vitamin D (Lin et al 2012 and isotocin (Chou et al 2011), as well as being under neurohumoral control (Perry et al 1984, Kumai et al 2012b. The existence of multiple hormonal regulators of ionic regulation highlights the importance of body fluid ionic homeostasis.…”
Section: Introductionmentioning
confidence: 99%